Sistem Informasi Penyewaan Kebaya, Jasa Make Up, Dekorasi, Fotografer Berbasis Website - Husni Mubarok; Dwi Diva Anjania; Nilan Wirda Naqiya; Sasi Wahyuningsih Maghfiroh; Akhris Fuadatis Sholikha; Safrina Muarrifah; Lilik Tanwirotul Fadlilah; Sigit Pamungkas (Jurnal Ilmiah Sistem Informasi Akuntansi, 2025)
This research discusses the development of a website-based information system for kebaya rental, make-up services, decoration, photography services designed to increase operational efficiency and customer satisfaction in the website-based kebaya rental, make-up, decoration and photographer services industry. This system is designed to make it easier for customers to search for, order and manage kebaya rentals, make-up services, decorations, photographers online, as well as allowing business owners to manage inventory and monitor demand in real-time. The results of this research also identify challenges in system development and provide technology-based solutions that are relevant to valid system black box testing. It is hoped that in the future this system can become a reference in digitizing traditional Indonesian clothing rental services.